2013
DOI: 10.19030/iber.v13i1.8354
|View full text |Cite
|
Sign up to set email alerts
|

Employee Training, Managerial Commitment And The Implementation Of Activity Based Costing; Impact On Performance Of SMEs

Abstract: This article examines the implementation of activity-based costing (ABC) in the SMEs sector in a developing country. The consequences of ABC on the evolution of management accounting and its impact on the accounting processes, particular as it relates to organizational cost performance has been a subject of discourse in the past two decades. This study provides some insight into the conspicuous paradox that in spite of the theoretical benefits of ABC, very few SMEs in South Africa adopt it and that a material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…As per previous research, this study has also found that user attitude has a positive significant relationship with the implementation of ABC among SMEs (Khozein & Dankoob, 2011;Dubihlele & Rundoro, 2014). Human capital development is essential for SMEs to provide them with the necessary knowledge, skills to employees to change user attitude and allow for a better usage of the ABC system in SMEs.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As per previous research, this study has also found that user attitude has a positive significant relationship with the implementation of ABC among SMEs (Khozein & Dankoob, 2011;Dubihlele & Rundoro, 2014). Human capital development is essential for SMEs to provide them with the necessary knowledge, skills to employees to change user attitude and allow for a better usage of the ABC system in SMEs.…”
Section: Discussionsupporting
confidence: 72%
“…According to Khozein and Dankoob (2011), user denial is one of the reasons affecting the implementation of ABC in their organisations. In the study by Dubihlele and Rundoro (2014) on 149 SMEs in South Africa, it was found that user attitude; managerial commitment was a precursor to the implementation of ABC of SMEs in South Africa. As a result, the following hypothesis was developed:…”
Section: Relationship Between the User Attitude And The Implementatiomentioning
confidence: 99%
“…In addition, Korir and Kepkebut (2016) state that committed employees have a sense of identification and belonging with an organisation. Dubihlela and Rundora (2014) affirm that an increase in global competition has forced businesses to ensure increased employee commitment in order to enable them to have a high level of excellence and competitiveness. Wasiu and Adelajo (2014) suggest that the importance of total rewards cannot be over emphasised.…”
Section: Background To the Studymentioning
confidence: 99%
“…At the same time, growing awareness of the importance of SMEs, which as reported earlier, represent more than ninety per cent of all employment around the world, has provided the impetus for further investigation of the potential for ABC to help SMEs become competitive and thrive in today's competitive market environment [64], [70][71][72][73][74][75][76][77][78][79][80][81][82] and for the development and use of software to implement ABC, such as 3Com Technology [83] or SAS (OROS System) [84]. The literature recognizes a number of potential benefits to SMEs from ABC.…”
Section: Abc and Smes: What The Research Saysmentioning
confidence: 99%
“…More accurate product costing and a meaningful financial and non-financial measure that aids in cost management and performance assessment [64,75,[85][86][87].…”
Section: Abc and Smes: What The Research Saysmentioning
confidence: 99%